Smart management and control system for liquid radioactive waste in hospitals using neural network techniques - S. Ahmed, Khaled; F. Sherif, Fayroz (International Journal of Engineering and Technology, 2020)
In tertiary hospitals where the nuclear medicine services have been introduced, the radioactive materials used in diagnosis and / or treatment need to be handled. The hospital design and medical planning should consider such these materials and their policy for treatment. The nuclear wastes have been divided into solid and liquid based on the used materials and for their half-life times which start from few minutes till reaching years. In our study, the most common radioactive liquid materials (wastes) have been treated by smart system. The system will detect the material of the waste via nuclear sensors and based on its HLT (activities), it will be distributed in two shielded storage tanks classified based on capacity then to the sewage treatment plant (STP) of the hospital after keeping for required times. The location and capacity of these tanks together with their monitoring and control system should be considered in design stage which determines the treatment processes. By applying our proposed technique on two hospitals, the results have reduced the storage tank capacity by 87% (reduction) and space area leading to cost reduction by 72% keeping the maximum level of safety.Â Â